Efektivitas penerapan model PBL berbasis wordwall - Mufadhilah, Badiatul; Sutriyani, Wulan (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The purpose of this study was to determine the effectiveness of the use of the Wordwall-based PBL model on the learning outcomes of mathematics in multiplication material for grade 3 students of SD Negeri 9 Jambu, Mlonggo. This study used a quantitative method and a one-group pretest and posttest design. By comparing the implementation before and after the application of the Wordwall-based Problem Based Learning (PBL) model. All grade 3 students became research subjects through saturated sample techniques. Collecting data through pretest, posttest. The results showed that before the application of Wordwall-based PBL was 67.34, while after the application it increased significantly to 89.06. This increase was strengthened by the results of the hypothesis with a significant value <0.001, which means less than 0.05. The conclusion is that there was a significant increase in understanding after the treatment of the Wordwall-based Problem Based Learning model was applied to mathematics learning on the multiplication material of whole numbers in grade 3 of SD Negeri 9 Jambu, Mlonggo.